موقع المواطنة في معادلة الاستقرار السياسي في الجزائر - شتيوي, علي; جراية, الصادق (University of Eloued جامعة الوادي, 2018)
عتبر المواطنة الفعالة عنصرا مهما في بناء الدولة الوطنية ،وتحقق الاستقرار الذي ينشده الجميع والذي بدونه لا وجود لدولة قوية ، تقوم المواطنة على جملة من المقومات والركائز، تكاد تكون نفسها بالنسبة لعامل الاستقرار السياسي الذي يتقاطع مع المواطنة في عناصر كثيرة. خلصت هذه الورقة البحثية الى ان المواطنة في الجزائر تنمو بشكل مقبول على مستوى النصوص والتشريعات ،لكنها بطيئة نوعا ما مقارنة بالقوانين بسبب تحديات تعيشها الجزائر ،لكنها قادرة على تجاوز تلك العقبات نظير ما تمتلكه الدولة والفرد الجزائري من مقومات وقدارت تأهله لبلوغ مستويات معتبرة.Effective citizenship is an important element in building the national structure of the state, as well as safeguarding the state and achieving the stability desired by all, without which there is no strong state. Citizenship is based on a set of elements and pillars, almost the same for the factor of political stability that intersects citizenship in many elements. Citizenship in Algeria is growing in an acceptable manner at the level of texts and legislation, but it is somewhat slow compared to the laws because of the challenges experienced by Algeria, but it is able to overcome those obstacles for what the state and the Algerian individual possess and the ability to qualify to reach significant levels.
The position of citizenship in the equation of political stability in Algeria
مقال
Keywords: المواطنة، الاستقرار السياسي، الجزائر، تحديات.; Citizenship, Political Stability, Algeria, challenges .